Impacts of Board Quality on Financial Performance in Conventional and Participatory Banks During and after the Covid-19 Crisis: Evidence from Emerging and Developing Countries - Achraf Haddad (STIE Malangkucecwara, 2023)
Going back to the governance literature, we found two equates on the correlation between the bank board and financial performance (FP). Firstly, we noticed that, in previous studies, the impacts of board quality on the financial performance of conventional and participatory (Islamic) banks were mixed, unstable, and sometimes contradictory. Secondly, we noticed a total absence of comparative studies showing the importance of the impact of the board composition quality on the financial performance of conventional and Islamic banks during and after the covid-19 crisis. To clarify the ambiguity, in this study, we compared in depth the impact of the board of directors (BOD) on the FP in two cited bank types. FP measures and board quality determinants are collected from 30 countries. The data concern 112 banks of each type that have published their reports regularly. Panel regressions were used to solve the ambiguity of the board quality’s impact on the FP of conventional and participatory banks in the agency theory framework during the period (2019-2022), giving us 448 observations in each sub-sample. Empirical results showed that the BOD negatively affects the FP of conventional banks (CBs), while that of participatory banks (PBs) has an ambiguous impact on their FP.